A poética de Fernando Pessoa nas canções-poemas de Maria Bethânia: um olhar semiótico - Sousa, Lívia Cavalcante Gayoso de (2019)
The combination between song and poetry stimulates several tendencies of investigations, since the objects allow various readings, from diverse theoretical conceptions. In the context of Brazilian Popular Music, the singer Maria Bethânia usually inserts poetic saying in her music-theatrical presentatios, making a significant interconnection between those elements. The product of that combination can be observed in her performances. At this juncture, Fernando Pessoa's poetics emerges as a recurring raw material, taken by the artist for the composition of what, in this research, has been conventionally called song-poems. Considering this context, the problem presented in the research is: how to analyze, through a semiotic perspective, Fernando Pessoa's poetics in Maria Bethânia's song-poems? The reseach, therefore, aims to present a possible reading of the song-poems, from the analysis of the literary text itself, using theorists such as Charles Sanders Peirce, Luiz Tatit and Algirdas Julius Greimas. Initially, there is a survey of critical fortune about Pessoa and Bethânia poetic-musical’s trajectories, as well as a study about the method used by Bethânia for set up her shows, based on a script constructed by the interconnection between music, poetry and theater, which brings us, as a consequence, a meanfull scenic manifestation, especially if it is compared, for example, to an isolated analysis of the elements music and poetry. In this perspective, the incidence of Pessoa’s poetry in Maria Bethânia’s discs and performances was investigated and, then, a semiotic reading of five song-poems extracted from this corpus was proposed. It is hoped, thereby, to contribute to the expansion of the senses – full of signs – produced by the song-poems performed by Maria Bethânia on the stages.